2017
DOI: 10.1016/j.urolonc.2016.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Prospective assessment and histological analysis of adherent perinephric fat in partial nephrectomies

Abstract: APF can be accurately predicted using radioclinical data as the MAP score, combined with sex, age, and waist circumference. APF is associated with increased operative time and blood loss without postoperative complications. Histological analysis finds larger adipocytes in APF without inflammatory infiltrate, and no difference in fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
66
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(80 citation statements)
references
References 36 publications
8
66
6
Order By: Relevance
“…Our study is the first to evaluate the incidence of APF in Asian individuals with renal malignancy. The incidence of APF in our study was 17%, which was lower than the incidence rates in previous studies of Western cohorts (30-55%) [3,4,6,13]. BMI was associated with APF in this Asian cohort as it was in the Western cohorts, although the mean BMI (24 kg/m 2 ) in our study was smaller than those in Western studies (29-33 kg/m 2 ) [5,6,12].…”
Section: Discussioncontrasting
confidence: 85%
See 4 more Smart Citations
“…Our study is the first to evaluate the incidence of APF in Asian individuals with renal malignancy. The incidence of APF in our study was 17%, which was lower than the incidence rates in previous studies of Western cohorts (30-55%) [3,4,6,13]. BMI was associated with APF in this Asian cohort as it was in the Western cohorts, although the mean BMI (24 kg/m 2 ) in our study was smaller than those in Western studies (29-33 kg/m 2 ) [5,6,12].…”
Section: Discussioncontrasting
confidence: 85%
“…The current results showed, however, that Asians had a lower incidence of APF at lower BMI levels compared to Caucasians. The predictors of APF other than MAP score reported in the Western cohorts were male gender, older age, obesity, waist circumference, and hypertension [3][4][5]. The current study indicated that male gender was a strong predictor of APF in multivariate analysis, although other metabolic factors, including older age, higher BMI, smoking habit, and history of hypertension were not associated with the presence of APF.…”
Section: Discussionmentioning
confidence: 42%
See 3 more Smart Citations